Incidence of Factors in Teaching Actions to Manage Antisocial Cyberbehaviour - Guillén-Gámez, Francisco David; Colomo-Magaña, Ernesto; Doddanavar, Indrajit; Ortiz-Padilla, Myriam (Springer, 2024)
With the proliferation of information and communication technologies (ICT), antisocial cyber-behavior has emerged, where teachers have a crucial role in the prevention and management of this behavior, focusing on developing actions that promote emotional and civic competences in students, where the skills and beliefs of the teacher are also a key piece. The purpose of this study was to develop an instrument to analyze the impact of these factors on teachers' actions to manage students' antisocial cyber-behaviors. A higher-order causal model was proposed following the partial least squares (PLS) method. The study was conducted with a sample of 835 active teachers from different educational stages from Spain, who taught in the following educational stages: Early Childhood Education, Primary Education, Secondary Education, Adult Education and Vocational Training. The main finding indicates that teachers' beliefs, coupled with their conflict resolution skills and approaches to fostering civic competencies, significantly influence (accounting for 50.30% of the real variance) their actions in managing cyber social behaviors. The study further reveals a connection between teachers' actions to enhance emotional and citizenship skills in students and their proficiency in conflict resolution. Consequently, the study underscores the importance of teachers possessing effective conflict resolution skills. These findings hold practical implications for education, as the developed causal model provides a deeper understanding of the factors influencing teachers' actions, facilitating targeted interventions in specific areas.
Keywords: Ciberacoso; Cyberhate; Cyberbehaviour; Socio-emotional and moral skills; Teacher training; Beliefs; Skills; Cultural and social implications